Comparative assessment of a virtual performance measure with self-report and performance-based outcomes in patients with hip osteoarthritis - Helen Razmjou; Suzanne Denis; Susan Robarts; Amy Wainwright; Patricia Dickson; Ania Roszkowski; John Murnaghan (BMC Musculoskeletal Disorders)
Abstract Background The purposes of this study were to examine the reliability and factorial and convergent validity of a virtual performance measure (VPM) in patients with osteoarthritis (OA) of the hip joint and to compare the known-group validity of the VPM with traditional self-report and performance-based outcomes. Methods The VPM score was based on the results of 10 videos showing increasing difficulty in performing specific functional tasks. Patients were requested to choose the video that best reflected their own level of function. Clinical presentation and radiological findings were documented. Self-report measures were the lower extremity functional score (LEFS) and pain scale. The performance-based measures were the 30- second Chair Stand Test (CST) and the 40-meter fast paced walk test (40 m FPWT) test. Results Data of 100 patients, 64 (64%) females, mean age: 67 ±10 were examined. The Cronbach’s alpha coefficient that examined internal consistency of the VPM total score was 0.88. Factor analysis showed two distinct domains. Moderate correlations were observed between the VPM total score and the LEFS, pain score, and 40 m FPWT (r > 0.50). The VPM and the LEFS were able to differentiate between candidates and non-candidates for hip arthroplasty and between those with and without assistive walking devices. There was no statistically significant difference between the overall accuracy of the VPM and LEFS in the area under the curve value (0.72 vs. 0.71) with respect to candidacy for surgery. Conclusions This study provides substantial evidence towards the validity and reliability of the VPM outcome measure in patients with moderate to severe OA of the hip joint. Digitally based outcome measures have the potential of enhancing remote measurement of functional difficulties in specific situations. Clinical trial number Not applicable.